2004
DOI: 10.1128/iai.72.9.5419-5432.2004
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Blood and Temperature Shift on Borrelia burgdorferi Gene Expression as Determined by Whole Genome DNA Array

Abstract: Borrelia burgdorferi undergoes differential gene expression during transmission from its tick vector to a vertebrate host. The addition of blood to a spirochete culture at 35°C for 48 h had a dramatic effect on gene expression of this organism. Utilizing B. burgdorferi whole genome DNA arrays, we compared the transcriptomes of the spirochetes following a 2-day temperature shift with blood and without blood. Using combined data from three independent RNA isolations we demonstrated that the addition of blood led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
253
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(271 citation statements)
references
References 69 publications
17
253
1
Order By: Relevance
“…Live imaging has revealed that this conception is an oversimplification. That Borrelia within unfed nymphal midguts are nonmotile is consistent with the quiescent metabolic state of organisms in this milieu (50)(51)(52)(53)(54) and is in line with observations made with crushed midguts dating back to the discovery of the Lyme spirochete as a tick-borne pathogen (49). On the other hand, our finding that the fed midgut is populated with replicating, but nonmotile, spirochetes was unexpected and runs counter to the prevailing notion, which equates metabolic activity with motility (58).…”
Section: Figuresupporting
confidence: 87%
“…Live imaging has revealed that this conception is an oversimplification. That Borrelia within unfed nymphal midguts are nonmotile is consistent with the quiescent metabolic state of organisms in this milieu (50)(51)(52)(53)(54) and is in line with observations made with crushed midguts dating back to the discovery of the Lyme spirochete as a tick-borne pathogen (49). On the other hand, our finding that the fed midgut is populated with replicating, but nonmotile, spirochetes was unexpected and runs counter to the prevailing notion, which equates metabolic activity with motility (58).…”
Section: Figuresupporting
confidence: 87%
“…on April 7, 2019 by guest http://jb.asm.org/ conditions that mimic the mammalian or tick hosts (11,17,53,64). qRT-PCR confirmed that there is upregulation of some of these genes (M. Caimano and J. Radolf, personal communication).…”
Section: Vol 190 2008 B Burgdorferi Flagellar Synthesis 1919mentioning
confidence: 82%
“…However, B. burgdorferi does specify Ն127 different putative lipoproteins, at least some of which are capable of promoting inflammatory responses (10,13,14). The lipoproteins expressed by B. burgdorferi are known to vary widely under the different environmental conditions they encounter during their natural infection cycle between arthropod and vertebrate hosts (15)(16)(17), but all of these proteins are predicted to possess similar triacyl modifications on their N-terminal cysteine residues (18). Studies from a number of laboratories have shown that these triacylated lipoproteins directly activate different host immune cells by signaling through TLR2 (19 -23) and the common intracellular adaptor molecule MyD88 (24,25).…”
mentioning
confidence: 99%